A Study on the Effect of Preservatives (Alum and Borax) and Plastic Packaging on weight Lost of Cabbage (Brassica Oleraseae) - Subardjo S.K (Balai Besar Industri Agro, 1986)
A study on the effect of preservative (alum and borax) and plastic packaging on the weight loss of cabbage (Brassica oleraceace) during cool storage has been done. The result showed that the shelf-life of cabbage can be prolonged to one month in cool temperature (9-10 degree celcius). The weight loss of cabbage during storage were 15.7% (without packaging), 5.6% (packed in perforated plastic bag) and 4.2% (packed in un-perforated plastic bag). The preservative didn't significantly have positive effects on the prevention of weight loss